2019
DOI: 10.1042/bsr20181919
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of hsa_circ_0004771 inhibits proliferation and induces apoptosis in breast cancer through activation of miR-653 by targeting ZEB2 signaling pathway

Abstract: Background: Circular RNAs (circRNAs) have been reported as the competing endogenous RNAs (ceRNAs) to sponge microRNAs (miRNAs) implicating in the initiation and progression of breast cancer. However, the functions of circRNAs in breast cancer have not been completely clarified. In the present study, we aimed to identify differentially expressed circRNAs in breast cancer tumor tissues, and their roles and downstream targets were investigated in the progression of breast cancer. Methods: High-throughput circRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 42 publications
(48 reference statements)
3
56
0
Order By: Relevance
“…20 More recent studies by Xie's group demonstrated that silencing of circNRIP1 restrained the proliferation and induced the apoptosis of MCF-7 and MDA-MB-231 cells by regulating the miR-653/Zinc finger E-box binding homeobox 2 axis. 21 Nevertheless, its precise role in hypoxia-induced chemoresistance in GC has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…20 More recent studies by Xie's group demonstrated that silencing of circNRIP1 restrained the proliferation and induced the apoptosis of MCF-7 and MDA-MB-231 cells by regulating the miR-653/Zinc finger E-box binding homeobox 2 axis. 21 Nevertheless, its precise role in hypoxia-induced chemoresistance in GC has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…circ_0004771 acted as a miRNA sponge to decrease expression of miR-653, this in turn targeted mesenchymal marker zinc finger E-box-binding homeobox 2 (ZEB2) gene expression by binding to its 3ʹ-untranslated region (3ʹUTR) of ZEB2 mRNA. 14 In addition, circAGFG1 was correlated with advanced clinical stage, poor prognosis and pathological grade of triple-negative breast cancer patients, mechanistically, circAGFG1 might directly sponge miR-195-5p, which targeted and repressed cyclin E1 expression. 15…”
Section: Major Features Of Circrnasmentioning
confidence: 97%
“…Currently, accumulating evidence demonstrated that aberrant expression miRNA was closely related to the development and progression of cancers, and could affect the cell's response to radiation [18,19]. MiR-653-5p targets 615 transcripts with conserved sites, containing a total of 662 conserved sites and 487 poorly conserved sites, and miR-653-5p can exert regulatory functions in mammalian evolution [20]. MiR-653-5p has been suggested to function as a tumor suppressor or tumor promoter in different cancers [21,22].…”
Section: Introductionmentioning
confidence: 99%